Pilot Study: Pemanas Untuk Thermal Cycler - Nugroho Budi Wicaksono; Sukma Meganova Effendi; Agatha Mahardika Anugrayuning Jiwatami (LPPM UNIVERSITAS PGRI SILAMPARI, 2023)
During the Covid-19 pandemic, DNA amplification technique – the Polymerase Chain Reaction (PCR) method became the gold standard for virus diagnosis and measuring the amount of viral target nucleic acid in a clinical sample and delivering quantitative results. This PCR method is implemented as Thermal Cycler or PCR machine. One of the main components in the Thermal Cycler is the heater. Three heaters, such as: Peltier Device 12715, Ceramic Heater PTC 12 VDC, and Customized Heater 12 VDC were tested for their performance by being connected to 3-well aluminium block. Two pieces of PTC Ceramic Heaters 12 VDC with a total power of 120 W showed the best performance compared to the other 2 heaters and were able to provide a heating ramp rate of 0,13 /second.